Are Inorganic Single-Molecule Magnets a Possibility? A Theoretical Insight into Dysprosium Double-Deckers with Inorganic Ring Systems - Kotrle, Kamil; Herchel, Radovan (Inorganic chemistry, 2019)
Computational studies of sandwich dysprosium double-decker complexes [Dy(L)2]+/3+ as candidates for single-ion magnets with several inorganic aromatic ring systems (P5-, N5-, B3N3H6, B3P3H6, B3S3H3) have been performed. The molecular structures were optimized with the TPSSh functional, and the ground state properties were investigated with the complete active space SCF method (CASSCF) complemented by the dynamic correlation dressed correction (DCD-CAS(2)) or NEVPT2. Besides the evaluation of the magnetic moment blocking barrier, the impact of the molecular vibration on the relaxation of magnetization was also inspected. We were able to make predictions about the performance of those molecules as single-molecule magnets, where estimated effective energy barrier, Ueff, values are as high as 1475 K in the case of [Dy(N5)2]-, which is the most anisotropic complex from our choice of studied compounds, making them a potentially very effective carbon-free alternative to organometallic double-decker dysprosocenium high-temperature single-molecule magnets.